2018
DOI: 10.1002/tafs.10017
|View full text |Cite
|
Sign up to set email alerts
|

Using Genetic and Phenotypic Comparisons to Evaluate Apparent Segregation among Kokanee Spawning Groups

Abstract: Genetic and phenotypic traits of spatially and temporally segregated kokanee Oncorhynchus nerka spawning groups in Lake Pend Oreille, Idaho, were compared to test for evidence of divergence on the basis of ecotype (stream spawners versus shoreline spawners) and spawn timing and to describe morphological, life history, and reproductive variation within and among groups. Early and late spawning runs were found to be reproductively isolated; however, there was no clear evidence of genetic differentiation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 87 publications
(148 reference statements)
0
14
1
Order By: Relevance
“…Despite the findings of Whitlock et al. (), we did not observe meaningful differences in FL, weight, or SGR between early‐run and late‐run kokanee. However, the current study focused on age‐0 fish and did not allow for potential differences in behavior or physiology that may manifest in wild adult fish.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Despite the findings of Whitlock et al. (), we did not observe meaningful differences in FL, weight, or SGR between early‐run and late‐run kokanee. However, the current study focused on age‐0 fish and did not allow for potential differences in behavior or physiology that may manifest in wild adult fish.…”
Section: Discussioncontrasting
confidence: 99%
“…Whitlock et al. () suggested that the observed differences in growth between adult (age‐2–4) early‐run and late‐run wild kokanee in LPO were due to differences in behavior and(or) physiology related to genetic differentiation between groups. Despite the findings of Whitlock et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproductive and genetic isolation of populations is one mechanism by which the coexistence of sympatric resident and migrant phenotypes can be maintained (e.g. Grabowski et al 2011;Turbek et al 2018;Whitlock et al 2018). This may occur spatially, for example, with the segregation by depth of different migratory phenotypes of Atlantic cod Gardus morhua during spawning (Grabowski et al 2011).…”
Section: Introductionmentioning
confidence: 99%